A Study on the Basic Drugs and Points for Point Application in Summer to Treat the Diseases with Attacks in Winter - 房繁恭 周雪忠 刘保延 王永炎 (Journal of Traditional Chinese Medicine, 2010)
Objective： To study the basic prescriptions of drugs and points for point application in summer to treat the diseases with attacks in winter and the law governing their compatibility. Methods： A database was set up by collecting and sorting out the relevant literature, and the analysis was made with the complex network. Results： It was found that Bai Jie Zi （白芥子 Semen Sinapis Albae）, Xi Xin （细辛 Herba Asari）, Gan Sui （甘遂 Radix Euphorbiae Kansui） and Yan Hu Suo （延胡索 Rhizoma Corydalis） were used as the basic prescriptions of drugs, Feishu （BL 13）, Dazhui （GV 14） and Shanzhong （CV 17） were selected as the basic prescription of points. Conclusion： The knowledge obtained from the complex networks on the basic prescriptions of drugs and points for point-application in summer to treat diseases with attacks in winter can provide a data support for working out operation norms and carrying on verification research.